Strategic decision-making of the company management using the findings of knowledge management - E. Svoboda (Agricultural Economics (AGRICECON), 2008)
This scientific paper shows the results formulated in the author's research focused on strategic decision-making of the company management in a new entrepreneurial environment resulting from changes caused by integration processes, the development of information technologies and globalisation factors. The goal of this paper is to publish the changes in behaviour of the management of the selected entrepreneurial entities resulting from new factors of changes affecting the entrepreneurial environment. This is reflected in the process of strategic decision-making of entrepreneurial entities in the necessity to use new methods of decision-making of the company management as a reaction to factors of the external as well as the internal environment. Rapid changes in particular in the external environment require the company management to select new approaches and methods of decision-making and to have a well conceived algorithm enabling a flexible response to customer wishes using the findings of knowledge management.